The Inter-Generational Transmission of Cognitive Abilities in Guatemala - Ma. Cecilia Calderón; John Hoddinott (Inter-American Development Bank (IDB), 2011)
This paper examines early childhood development (ECD) outcomes and their association with family characteristics, investments, and environmental factors, with particular emphasis on the inter-generational transmission of cognitive abilities. The paper examines the causal relationship between parental cognitive abilities and ECD outcomes of their offspring using a rich data set from rural Guatemala that can account for such unobservable factors. A 10 percent increase in maternal Ravens scores increase childrens Ravens scores by 7. 8 percent. A 10 percent increase in maternal reading and vocabulary skills increases childrens score on a standard vocabulary test by 5 percent. Effects are larger for older children, and the impact of maternal cognitive skills is larger than for paternal skills.
Keywords: J12; J24; N36; 330